Exercise benefits in cardiovascular disease: beyond attenuation of traditional risk factors. Issue 12 (December 2018) - Fiuza-Luces, Carmen; Santos-Lozano, Alejandro; Joyner, Michael; Carrera-Bastos, Pedro; Picazo, Oscar; Zugaza, José; Izquierdo, Mikel; Ruilope, Luis; Lucia, Alejandro
Abstract Despite strong scientific evidence supporting the benefits of regular exercise for the prevention and management of cardiovascular disease (CVD), physical inactivity is highly prevalent worldwide. In addition to merely changing well-known risk factors for systemic CVD, regular exercise can also improve cardiovascular health through non-traditional mechanisms. Understanding the pathways through which exercise influences different physiological systems is important and might yield new therapeutic strategies to target pathophysiological mechanisms in CVD. This Review includes a critical discussion of how regular exercise can have antiatherogenic effects in the vasculature, improve autonomic balance (thereby reducing the risk of malignant arrhythmias), and induce cardioprotection against ischaemia–reperfusion injury, independent of effects on traditional CVD risk factors. This Review also describes how exercise promotes a healthy anti-inflammatory milieu (largely through the release of muscle-derived myokines), stimulates myocardial regeneration, and ameliorates age-related loss of muscle mass and strength, a frequently overlooked non-traditional CVD risk factor. Finally, we discuss how the benefits of exercise might also occur via promotion of a healthy gut microbiota. We argue, therefore, that a holistic view of all body systems is necessary and useful when analysing the role of exercise in cardiovascular health. The benefits of regular exercise extend beyond its effect on cardiovascular disease (CVD) risk factors. In this Review, the authors outline the non-traditional mechanisms underlying the benefits of exercise in CVD and highlight the importance of a holistic view of exercise in cardiovascular health. Key points Regular exercise induces antiatherogenic adaptations in vascular function and structure, irrespective of traditional cardiovascular disease (CVD) risk factors. Regular exercise training improves cardiac parasympathetic regulation, thereby conferring protection against malignant arrhythmias, and also provides cardioprotection against ischaemia–reperfusion injury. Muscle-derived myokines are responsible for many of the beneficial effects of exercise, particularly by promoting a healthy anti-inflammatory milieu. Exercise can improve myocardial regeneration capacity, in part through stimulation of circulating angiogenic cells. Loss of muscle strength and mass is a forgotten hallmark of — and, in fact, a risk factor for — CVD that can be largely reversed with resistance (strength) training, including in elderly individuals. Regular exercise can promote a healthy gut microbiota while protecting the permeability and function of the gut barrier.